Talent identification and selection process of outfield players and goalkeepers in a professional soccer club - Gil, S. M.; Zabala-Lili, J.; Bidaurrazaga-Letona, I.; Aduna, B.; Lekue, J. A.; Santos-Concejero, J.; Granados, C. (Journal of Sports Sciences, 2014)
The aim of this study was to analyse the talent identification process of a professional soccer club. A preselection of players (n = 64) aged 9-10 years and a final selection (n = 21) were performed by the technical staff through the observation during training sessions and matches. Also, 34 age-matched players of an open soccer camp (CampP) acted as controls. All participants underwent anthropometric, maturity and performance measurements.